2000
DOI: 10.1016/s0001-2092(06)62019-x
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenologic Study of How Perioperative Nurses Perceive Their Work World

Abstract: As health care facilities restructure and downsize, many are evaluating the value of RNs as members of the health care team. While many studies have been done about how health care systems measure value, no studies have been found that focus on areas of concern from the perspective of nurses who actually work in the OR. This article details the results of a phenomenologic study that used one-on-one interviews to ask five perioperative nurses how they perceive their work world. By telling the nurses stories, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Within these two broad domains, 12 articles 16–27 described categories of specialized knowledge while the remaining nine illustrated categories related to human factors 28–36 . Of the 21 studies we reviewed, eight of the studies were conducted in Australia, 16,17,20–23,26,27 eight in North America, 19,24,29–31,34–36 four in Great Britain 18,25,28,32 and one in Finland 33 . The majority of research articles (n = 13) used qualitative methods, 16–19,22–26,28,29,33,34 seven used quantitative methods, 21,27,30–32,35,36 and one used a mixed methods approach 20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within these two broad domains, 12 articles 16–27 described categories of specialized knowledge while the remaining nine illustrated categories related to human factors 28–36 . Of the 21 studies we reviewed, eight of the studies were conducted in Australia, 16,17,20–23,26,27 eight in North America, 19,24,29–31,34–36 four in Great Britain 18,25,28,32 and one in Finland 33 . The majority of research articles (n = 13) used qualitative methods, 16–19,22–26,28,29,33,34 seven used quantitative methods, 21,27,30–32,35,36 and one used a mixed methods approach 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 21 studies we reviewed, eight of the studies were conducted in Australia, 16,17,20–23,26,27 eight in North America, 19,24,29–31,34–36 four in Great Britain 18,25,28,32 and one in Finland 33 . The majority of research articles (n = 13) used qualitative methods, 16–19,22–26,28,29,33,34 seven used quantitative methods, 21,27,30–32,35,36 and one used a mixed methods approach 20 . Subsumed within the two broad domains of competence are the following categories: practical knowledge, aesthetic knowledge, communication, teamwork, coordination, and leadership.…”
Section: Resultsmentioning
confidence: 99%
“…Capturing the artistic and human nature of nursing has proved to be difficult when used as the defining characteristic of nursing. Numerous authors have identified caring characteristics of OR nurses 6,12–19 . These characteristics have included compassion, kindness, gentleness, friendliness, cheerfulness, recognition of the patient as a person with individual needs and the attitude that suggests nothing was too much trouble.…”
Section: Caring and Technologymentioning
confidence: 99%
“…Numerous authors have identified caring characteristics of OR nurses. 6,[12][13][14][15][16][17][18][19] These characteristics have included compassion, kindness, gentleness, friendliness, cheerfulness, recognition of the patient as a person with individual needs and the attitude that suggests nothing was too much trouble. Stein-Parbury notes that the most current understanding of caring is as an '.…”
Section: Caring and Technologymentioning
confidence: 99%
“…Abundant quantitative research has been conducted on variables such as job satisfaction and perceived stress, preselected by the researchers. Few studies have been done on areas of concern from the perspectives of RNs about caring for patients (Chard, 2000; Jennings & McClure, 2004; Van Maanen, 1990). As Chang et al (2002) noted: “Lack of information about nursing practice patterns may limit the ability of nursing leadership to develop and evaluate innovative approaches to improving the quality of nursing care” (p. 406).…”
mentioning
confidence: 99%